A revision of the Cainozoic Cerithiidae and Plesiotrochidae (Mollusca: Caenogastropoda) of the Paratethys Sea (Europe, Asia) - Harzhauser, Mathias; Guzhov, Aleksandr; Landau, Bernard (Zootaxa, 2025)
We document 61 Cerithiidae and 5 Plesiotrochidae species from the Late Oligocene to Late Miocene of the Paratethys Sea. The maximum diversity with 24 species occurred during the early Middle Miocene in the Central Paratethys Sea (early/middle Badenian), coinciding with the Langhian part of the Miocene Climate Optimum. In the Eastern Paratethys the maximum diversity was established simultaneously during the Chokrakian, peaking in nine species. However, the faunistic correlation between the Central and Eastern Paratethys seas was negligible during most of the Miocene. Only during the latest Badenian/Konkian and early Sarmatian/Volhynian, two species occurred in both seas. The beginning of the disintegration of the Central Paratethys Sea following the Badenian Salinity Crisis, is expressed by an endemicity of ~50% of the Cerithiidae faunas in the Fore-Carpathian Basin and the Moldovan Platform, where many endemic species evolved. In total we traced more than 230 species-level names for Paratethyan species originally established in ‘cerithiids’. Of these, 66 are accepted herein as valid Cerithiidae and Plesiotrochidae species. Bittium amibouei sp. nov., Bittium badzoshviliae sp. nov., Bittium merklini sp. nov., Bittium foedum sp. nov., Bittium grinzingense sp. nov., Bittium krenni sp. nov., Bittium praescabrum sp. nov., Bittium rossicum sp. nov., Bittium tani sp. nov., Bittium walaszczyki sp. nov., Cerithidium iljinae sp. nov., Thericium basilicum sp. nov., Thericium bursucense sp. nov., Thericium chamaeleo sp. nov., Thericium miodacicum sp. nov., Thericium posidoniaphilum sp. nov., Thericium vovkotrubense sp. nov., Thericium zhizhchenkoi sp. nov., Hemicerithium caucasicum sp. nov., and Hemicerithium kovacsi sp. nov., are described as new species. Bittium nabokovorum Guzhov nom. nov., Pithocerithium mediolanionense nom. nov. and Pithocerithium putzgruberi nom. nov. are introduced as new names for Bittium binodulosum Guzhov, 2022 [non Yokoyama, 1920], Cerithium imperfectum Sieber, 1937 [non Deshayes, 1833] and Cerithium europaeum May. var. acuminata Schaffer 1912 [non Zekeli, 1852]. We provide additions and corrigenda to the paper of this series on Potamididae and Batillariidae by Harzhauser et al. (2023a). Theodisca Harzhauser, Guzhov & Landau, 2023 [Potamididae] [non Theodisca Müller, 1858 [Polychaeta] is replaced by Theodiscella nom. nov.